2014
DOI: 10.1158/1078-0432.ccr-12-3680
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathways: PI3K Pathway Phosphatases as Biomarkers for Cancer Prognosis and Therapy

Abstract: Cancer research has seen tremendous changes over the past decade. Fast progress in sequencing technology has afforded us with landmark genetic alterations, which had immediate impact on clinical science and practice by pointing to new kinase targets, such as PI 3-Kinase, the EGF receptor or BRAF. The PI 3-Kinase pathway for growth control has emerged as a prime example for both oncogene activation and tumor suppressor loss in cancer. Here, we discuss how therapy using PI 3-kinase pathway inhibitors could benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 75 publications
0
22
0
Order By: Relevance
“…Downstream of these kinases, lipid phosphatases are critical to PI(3)P homeostasis. The INPP4b phosphatase, which produces PI(3)P from PI(3,4)P 2 , has been identified as a tumor suppressor (Chen et al, 2014; Fedele et al, 2010; Gewinner et al, 2009), consistent with a role in supporting PTEN via PI(3)P production. Finally, the Myotubularin phosphatase, which dephosphorylates PI(3)P (Taylor et al, 2000), is essential for cell survival through AKT signaling (Razidlo et al, 2011), consistent with suppression of the PI(3)P/PTEN axis.…”
Section: Discussionmentioning
confidence: 77%
“…Downstream of these kinases, lipid phosphatases are critical to PI(3)P homeostasis. The INPP4b phosphatase, which produces PI(3)P from PI(3,4)P 2 , has been identified as a tumor suppressor (Chen et al, 2014; Fedele et al, 2010; Gewinner et al, 2009), consistent with a role in supporting PTEN via PI(3)P production. Finally, the Myotubularin phosphatase, which dephosphorylates PI(3)P (Taylor et al, 2000), is essential for cell survival through AKT signaling (Razidlo et al, 2011), consistent with suppression of the PI(3)P/PTEN axis.…”
Section: Discussionmentioning
confidence: 77%
“…29,30 In a similar fashion, the CNS has been described as an immune privileged site in which direct stimulation or recruitment of cytotoxic T-cell populations may be less robust compared with extracranial tumor sites treated with immunotherapy. 7,32 Encouragingly, the median OS of patients with MBM in the current data set appears much improved compared with historical data. 7,32 Encouragingly, the median OS of patients with MBM in the current data set appears much improved compared with historical data.…”
Section: Discussionmentioning
confidence: 78%
“…31 Another possibility is that neither class of therapies directly target the biology underlying brain tropism for some melanoma tumors. 7,32 Encouragingly, the median OS of patients with MBM in the current data set appears much improved compared with historical data. Davies et al reported a median OS of 4.7 months after a diagnosis of MBM in patients who developed MBM during clinical trial participation between 1986 and 2004.…”
Section: Discussionmentioning
confidence: 78%
“…We showed previously that the Akt phosphatase Phlpp2 (35, 36), but not the Phlpp1 homolog, is specifically induced by Akt pathway activation to limit the signaling output ((15), and reviewed in (37)). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%